Oil and Mexican Foreign Policy - Grayson, George W., 1938-2015 (Book collections on Project MUSE., 1988)
Following up on his earlier "The Politics of Mexican Oil", Grayson focuses on the impact of oil on Mexican foreign policy since 1976. He argues that availability of oil significantly altered Mexico's perception of its international role, with importantresults for domestic politics and U.S.-Mexican relations. Grayson marshals plenty of evidence for his thesis, including many interviews with Mexicans and other nationalities. He concludes that the future relationship between Mexico and the United States is likely to be contentious. Excellent, lucid, and jargon free. Highly recommended for the informed and specialists.